60.7k views
0 votes
If f(x) = x - 3, g(x) = 2x - 6, and h(x) = x^2 - 6x + 9, then (h - fg)(-1)=

If f(x) = x - 3, g(x) = 2x - 6, and h(x) = x^2 - 6x + 9, then (h - fg)(-1)=-example-1

1 Answer

3 votes

The function h - fg is given by:


\begin{gathered} (h-fg)(x)=h(x)-(fg)(x) \\ =h(x)-f(x)\cdot g(x) \end{gathered}

Therefore,


\begin{gathered} (h-fg)(x)=(x^2-6x+9)-(x-3)(2x-6) \\ =(x-3)^2-2(x-3)^2 \\ =-(x-3)^2 \end{gathered}

Therefore,


(h-fg)(-1)=-(-1-3)^2=-(-4)^2=-16

Therefore,

(h - fg)(-1) = -16

User Martijn Vissers
by
5.9k points